Gender awareness and patriarchal relations on merariq kodeq culture in Ampenan Mataram - Aryati, Risma Ade; Susanti, Emy (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
Early marriage is still a central issue in Indonesian society, including in Ampenan, Mataram, West Nusa Tenggara. This study aims to reveal gender awareness and patriarchal relations in merariq kodeq culture in Ampenan Mataram. Sylvia Walby's patriarchy theory is used as a tool to analyze. This study uses a qualitative research method with a phenomenological approach. Subject of this research is women who are married for the first time and are under 19 years old. The results showed that merariq kodeq occurs through a long process of Sasak tradition that still survives today. The tradition also has implications for the emergence of patriarchal relations in domestic life. This study concludes that patriarchal relations in early marriage perpetuate domination not only in the private sector but also in the public sector. Patriarchal relations are also the root cause of domestic violence.